Gustav Shpet - Tihanov, Galin (Primerjalna književnost, 2006)
The paper reviews Gustav Shpet's immersion in Russian Symbolism, his contacts with the Imagists, his contribution to the work of the Moscow Linguistic Circle and the study of literature at GAKhN. In the final section an analysis of Shpet's career as a translator is offered.
Keywords: Špet, Gustav, 1879-1937; ruska književnost; Russian literature; literarna teorija; literary theory; literarna estetika; simbolizem; imaginizem; moskovski lingvistični krožek